Impact of Flow Boiling on Blast Furnace Tuyere Life: A Designer's Perspective. Issue 4 (28th October 2021) - Chatterjee, Rajeswar; Nag, Samik; Kundu, Subhashis; Ghosh, Ujjal; Singh, Uttam; Chandra, Sanjay
Abstract : Water‐cooled copper tuyeres of blast furnace are subjected to intense thermal conditions. Several modifications are attempted to prevent tuyere failure as the impact of failure is severe. What has, however, gone unnoticed is the peak "Cold face" temperature in tuyere and its implication. Numerical model incorporating water flow and conjugate heat transfer with a feature to identify onset of boiling by analytical correlations is developed. It is ascertained that, in tuyeres, the temperature of the Cold face exceeds the saturation temperature at the prevailing pressure by an amount high enough to cause nucleate boiling. The implication of the onset of boiling is discussed and a design modification is suggested by changing the aspect ratio of cooling passage. The impact of velocity distribution to achieve lower peak "Cold face" temperature is discussed. Modified design shows almost zero boiling prone zone for the range of operating parameters studied. Fourteen modified tuyeres are placed alongside original designed tuyeres in an blast furnace. The newly designed tuyeres outperform their counterparts. This approach to identifying and suppressing boiling of water in the cooling channel—a hitherto neglected phenomenon—gives an additional input towards designing a more robust tuyere. Abstract : Identification and implication of onset of nucleate boiling in a Tuyere cooling channel is discovered. A feature coupled with conjugate heat transfer formulation is put forward to predict the onset. A design solution suppressing the cause of the onset is detailed out. The concept of mitigation is explained with correlating velocity distribution and heat load.